Perancangan Ulang Ruas Jalan Wonosari - Semin STA 4+000 - 8+000, Gunungkidul Yogyakarta - Handoko (Jurusan T. SIpil Fakultas Teknik UMY, 2014)
Perancangan Ulang Ruas Jalan Wonosari - Semin STA 4+000 - 8+000, Gunungkidul Yogyakarta